THE ROLE OF CONSCIENCE: IS IT ALWAYS TO FOLLOW THE HIERARCHICAL MAGISTERIAL TEACHINGS? - Tirimanna, Vimal (Asian Horizons, 2016)
Although the Vatican II assigned to a properly formed conscience of a person, the full dignity it deserves (as so consistently taught in the Catholic moral tradition), during the past few decades, there is a growing tendency within the Catholic fold to uphold the naïve, but erroneous view that conscience has to always simply and blindly follow what the hierarchical magisterium teaches. This essay is an effort to dispel such erroneous opinions, using the Catholic moral tradition and the official hierarchical teachings themselves. While recognizing the positive, indispensable role the hierarchical magisterium has to play in forming a believer’s conscience, the article highlights the need for both the conscience and the hierarchical magisterium to be in constant dialogue in their search for moral truth.